Konstruksi Kebutuhan Keinginan pada Iklan Fast Fashion Dalam Perspektif Horkheimer - Loppies, Imelda Jaqualine; Adam, Arlin; Kamaruddin, Syamsu A. (Universitas Djuanda Bogor, 2026)
The penetration of digital technology over the past two decades has transformed patterns of public consumption, including in Biak Numfor Regency. This study aims to critically examine how exposure to fast fashion advertising on digital platforms reproduces the mechanisms of the culture industry and instrumental rationality as conceptualized by Max Horkheimer, and how these processes shape public consciousness, preferences, and consumption practices. This research employs a descriptive qualitative approach, with data collected through in-depth interviews with purposively selected informants and observations of social media usage patterns. The findings indicate that Facebook, Instagram, TikTok, and TikTok Shop serve as the primary channels for the dissemination of fast fashion advertisements. The high frequency of advertisement exposure, particularly following search or purchase activities, demonstrates the operation of algorithmic personalization as a manifestation of instrumental rationality within digital capitalism. From a Critical Theory perspective, this condition represents the transformation of the culture industry into the digital sphere, where platforms not only market products but also construct false needs and normalize rapid consumption as part of a modern lifestyle. The study further reveals that exposure to fast fashion advertising contributes to the commodification of identity and the reproduction of consumerist values, gradually shifting the community’s collective orientation toward individualistic and symbolic logic. Clothing is no longer understood merely as a functional necessity but as a means of social legitimation mediated by platform capitalism. These findings affirm the subtle operation of ideological domination through digital media and underscore the importance of strengthening critical literacy in responding to the expansion of global consumer culture.